2004
DOI: 10.1103/physrevlett.93.057002
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Superconducting Transition Temperature inNb/PermalloyBilayers by Controlling the Domain State of the Ferromagnet

Abstract: In (S/F) hybrids the suppression of superconductivity by the exchange field h(ex) of the ferromagnet can be partially lifted when different directions of h(ex) are sampled simultaneously by the Cooper pair. In F/S/F trilayers where the magnetization directions of the F layers can be controlled separately, this leads to the so-called spin switch. Here we show that domain walls in a single F layer yield a similar effect. We study the transport properties of Ni(0.80)Fe(0.20)/Nb bilayers structured in strips of di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 136 publications
(63 citation statements)
references
References 21 publications
2
61
0
Order By: Relevance
“…A special remark concerns the point that no traces are found of an enhancement of the superconductivity by domain averaging from Cooper pairs, as found before both in CuNi-and Py-based devices, 6,7 and also more recently in a different set of Py-based devices. 20 In particular, for the large-area bilayer sample BL20, enhanced superconductivity in the domain state might have been expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A special remark concerns the point that no traces are found of an enhancement of the superconductivity by domain averaging from Cooper pairs, as found before both in CuNi-and Py-based devices, 6,7 and also more recently in a different set of Py-based devices. 20 In particular, for the large-area bilayer sample BL20, enhanced superconductivity in the domain state might have been expected.…”
Section: Discussionmentioning
confidence: 99%
“…6 This is basically due to the fact that Cooper pairs break less easily when they sample an inhomogeneous exchange field, which can be considered a lateral variant of the spin-valve effect. 7 For spin-valve systems with strong ferromagnets, the situation is more complicated. In a number of reports, with magnets such as Ni ͑Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally, it will be smaller near the domain wall and we may expect that superconductivity would be more robust near them. The local increase of the critical temperature in presence of magnetic domains was observed experimentally in Ni 0.80 Fe 0.20 /Nb bilayers (with Nb thickness around 20 nm) 7 , and it was attributed to DWS formation.…”
Section: Introductionmentioning
confidence: 87%
“…It is interesting to remark that this difference would not be observable in Nb/Py, since in that case the switching was in such a small field range ͑order 10 −4 T͒ that a possible averaging difference would go unnoticed. 22 That leaves an explanation for the kink feature in R s ͑H͒. Looking again at Fig.…”
Section: A Results On the 2 M Bridgementioning
confidence: 99%
“…Changes in T c are mostly less than 10 mK, and in bilayer experiments involving Py it was demonstrated that the relative enhancement of superconductivity over domains walls resulted in a similarsized increase in T c . 22 For the weak ferromagnets such as Cu 1−x Ni x ͑with x in the range 0.5-0.6͒, which played such an important role both in demonstrating junctions and ͑appar-ent͒ spin switching, it was not yet investigated whether domains in the F layer can enhance superconductivity in a similar way.…”
Section: Introductionmentioning
confidence: 99%